(untitled) (Al-Academy, 2024)
Artificial intelligence systems programs contribute to the creation of ideas, programs and methods through the computer that are actually achieved in terms of goals. This research discusses the impact of the development of the fields of art, including the art of contemporary graffiti through the Pixler digital photographer, and accordingly consists of the first chapter of The research problem, the goal of the research, its limits, and the terminology of this study. The second chapter consists of the first section, entitled the generation system in artificial intelligence programs, and the second section, artificial intelligence programs in contemporary graffiti, and then the research indicators. As for the third chapter, which consisted of the research procedures and methodology, the research community, and the reasons for choosing the samples, leading to the descriptive analysis that is compatible with the goal of the research, as for the fourth chapter, the results are presented, which are linked to the research problem, conclusions, sources, and references. One of the results of the research came, the Pixler program feature is a feature in which it is divided the image of the original model is divided into several different snapshots, up to ten slides out of one snapshot, and then it is transformed into an application proposal through which the manual printing formula is repeated within the mechanism of this artificial program